Argentina en el siglo XX - Franco Eugenio Nanni; Adriana Fátima Panico (Colegio de Economistas de A Coru\~na, 2010)
– In previous work ('Interpreting the crisis'), analyzed the economic and financial crisis of 2008-2009 and its similarities to other crises in the twentieth century in the U.S. and the UK. In this paper we analyze and interpret the situation in Argentina and other Latin American countries. For the analysis we use gross output series, we calculate growth rates and inflation and provide a brief comparison with other Latin American countries. We use the structural approach models state space as econometric statistical methodology to detect structural changes in the series over the century.
Keywords: 330